On a new approach to convolution constructions - S. B. Yakubovich; Shyam L. Kalla (International Journal of Mathematics and Mathematical Sciences)
In this paper we establish some new approach to constructing convolution for general Mellin type transforms. This method is based on the theory of double Hellin-Barnes integrals. Some properties of convolutions and several examples are given.